Assessing psychological flexibility and mental health in adults: The Psy-Flex European Portuguese version. - Cunha, Marina (2024)
The current study developed the European Portuguese version of the Psy-Flex. Its factor structure was studied through confirmatory factor analysis in a large community sample (N = 700) and cross-validated in calibration and validation samples created from the original sample. Confirmatory factor analyses confirmed a sample and sex-invariant single-factor structure with a very good fit to the data. These analyses supported good reliability and test-retest reliability in the PsyFlex European Portuguese version. Correlations with related and unrelated constructs were indicative of convergent and predictive validity. Because it is short and easy-to-use, it reduces participant burden and may be useful in clinical and research settings. The European Portuguese Psy-Flex version will allow the broadening of research possibilities not only in Portugal but also across cultural contexts.